Optimization of Fish Based Extruded Product by Twin Screw Extrusion using Response Surface Methodology and Shelf life Evaluation - Kamalakanth, C. K.; Joshy, C. G.; Varkey, Jones; Ravishankar, C. N.; Gopal, T. K. Srinivasa (Fishery Technology, 2025)
Effect of extrusion conditions like temperature, screw speed, and moisture content of the fish incorporated extruded snack on specific mechanical energy (SME) and texture were evaluated and optimized by using response surface methodology. A central composite design with 20 runs was formulated for the experiment and the quadratic model was most suitable for explaining the changes of dependent variables with respect to independent variables. It was found that as the temperature increased, SME and texture decreased; whereas, SME was directly proportional with screw speed. There was a decrease in the SME and increase in texture as the moisture content increased. Maximum desirability value of 0.873 revealed that the screw speed of 380 rpm at a temperature of 140°C and 17% moisture content were optimum for the development of fish incorporated extruded snack and values for SME and texture were 251.26 KJ kg-1 and 9.86 N, respectively. Storage study of fish-incorporated extruded snack developed at optimized conditions revealed that thiobarbituric acid and texture were increased with storage period. Similarly, redness of the sample increased while whiteness and yellowness of the sample were decreased with storage. At ambient temperature (28±1°C), the product had a shelf life of 4 months.